Spontaneous Calyceal Rupture from an Unusual Source - Basil Razi; Dane Cole-Clark; Duncan Self; Edward Latif (Société Internationale d’Urologie Journal)
A computed tomography intravenous pyelogram (CT IVP) is a very common investigation performed for a wide range of urological presentations such as abdominal pain and haematuria. We report a rare case of spontaneous calyceal rupture and associated haemorrhage during a CT.